Ask Question
24 December, 12:38

Solve the following equation

(7X3+4X2+3X+2) + (2X2+X+5) =

+3
Answers (1)
  1. 24 December, 13:17
    0
    The way it's written it's

    Simplify the following:

    7 X^3 + 4 X^2 + 2 X^2 + 3 X + X + 2 + 5

    Grouping like terms, 7 X^3 + 4 X^2 + 2 X^2 + 3 X + X + 2 + 5 = 7 X^3 + (4 X^2 + 2 X^2) + (3 X + X) + (2 + 5) : 7 X^3 + (4 X^2 + 2 X^2) + (3 X + X) + (2 + 5)

    4 X^2 + 2 X^2 = 6 X^2:

    7 X^3 + 6 X^2 + (3 X + X) + (2 + 5)

    3 X + X = 4 X:

    7 X^3 + 6 X^2 + 4 X + (2 + 5)

    2 + 5 = 7:Answer: 7 X^3 + 6 X^2 + 4 X + 7
Know the Answer?